Islam and Muslims in Germany - Hamarneh, Ala al-; Thielmann, Jörn (Muslim minorities, 2010)
In the European discourse of post 9/11 reality, concepts such as "Multiculturalism", "Integration" and "European Islam" are becoming more topical. This volume reflects the variety of Muslim social practices and life-worlds in Germany. It presents theoretical approaches and analyses of a mosaic of communities, cultures, and social practices